Synthetic Strategies for Variably Substituted Ruthenium–Imidazophenanthrolinium Complexes. Issue 5 (28th October 2014) - Petermann, Lydia; Staehle, Robert; Pilz, T. David; Sorsche, Dieter; Görls, Helmar; Rau, Sven
Abstract: The synthesis of several symmetric and asymmetric substituted imidazophenanthrolinium ligands and their corresponding ruthenium polypyridyl complexes was achieved by applying a newly designed synthetic concept. By testing different moieties, the advantages and limits of the synthetic approach could be defined. The substitution pattern on the imidazolium moiety has no significant influence on the structural aspects of the imidazophenanthrolinium backbone or on the photophysical properties of the ruthenium compounds. Given that imidazolium salts act as precursors for N‐heterocyclic carbenes, the reported results provide the basis for the design of highly efficient oligonuclear photocatalysts. Abstract : Different synthetic strategies are investigated for the synthesis of variably substituted ruthenium–imidazophenanthrolinium complexes. Structural and preliminary photochemical characterizations suggest that substitution patterns can be altered without influencing the photochemical properties.